2023
DOI: 10.3390/v15030804
|View full text |Cite
|
Sign up to set email alerts
|

The Antiviral Compound PSP Inhibits HIV-1 Entry via PKR-Dependent Activation in Monocytic Cells

Abstract: Actin depolymerization factor (ADF) cofilin-1 is a key cytoskeleton component that serves to lessen cortical actin. HIV-1 manipulates cofilin-1 regulation as a pre- and post-entry requisite. Disruption of ADF signaling is associated with denial of entry. The unfolded protein response (UPR) marker Inositol-Requiring Enzyme-1α (IRE1α) and interferon-induced protein (IFN-IP) double-stranded RNA- activated protein kinase (PKR) are reported to overlap with actin components. In our published findings, Coriolus versi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…The actin cytoskeleton plays important roles in most cellular processes, including mechanical support, cell migration, differentiation, and signaling pathways. F‐actin contributes to morphology, trafficking, migration, and adhesion through continuous polymerization and depolymerization (Alvarez‐Rivera et al., 2023 ). Cucurbitacins generally affect the organization of the actin cytoskeleton, causing changes in the cells' normal actin dynamics and actin aggregate formation.…”
Section: Discussionmentioning
confidence: 99%
“…The actin cytoskeleton plays important roles in most cellular processes, including mechanical support, cell migration, differentiation, and signaling pathways. F‐actin contributes to morphology, trafficking, migration, and adhesion through continuous polymerization and depolymerization (Alvarez‐Rivera et al., 2023 ). Cucurbitacins generally affect the organization of the actin cytoskeleton, causing changes in the cells' normal actin dynamics and actin aggregate formation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, PSP demonstrates the ability to extend its anti-cancer effects towards the immune system by inhibiting HIV-1 replication in THP1 and peripheral blood mononuclear cells through the upregulation of antiviral chemokines [ 187 ]. It has also been observed to target the entryway through overlapping signaling between UPR marker IRE1α and PKR in monocytes [ 188 ]. This review provides deeper insight into common overlapping pathways that are shared among predominant oncogenic disturbances as well as triggered during HIV-1 infections ( Figure 3 ).…”
Section: Signaling Pathways In Cancer: Mutual Crosstalk Between Er St...mentioning
confidence: 99%
“…Accordingly, new molecular insights into how UPR, IFN-IP, and cytoskeletal events interact are provided by the current study. Interestingly, the information presented in the article suggested that PSP may be utilized as a natural alternative to stop HIV-1 entrance [ 10 ]. In a communication article authored by Zhu and collaborators, the mechanism of the molecular recognition of the HIV-1 gp120 V3 loop by the coreceptor CXC chemokine receptor 4 (CXCR4) was investigated using a construct containing the V3 loop (full-length).…”
mentioning
confidence: 99%